CONCEPTUAL CHARACTER EDUCATION MODEL IN SCHOOL - Khambali, Khambali; Komala, Ela; Arifin, Bambang Samsul; Hasanah, Aan (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this research is to understand various development models in the cultivation of character values in schools. The approach used is a qualitative approach with literature study techniques. Based on the findings and analysis, it was found that the concept of character education development in schools is a model for inculcating character values consisting of teaching, habituation, and imitation, in its implementation the Tadzkirah, Istiqomah, Iqra - (Fikir - Zikir) Model is the right model for used in character education learning, as well as CTL. Furthermore, the character education process needs to involve all components (stakeholders), including the education component itself, and the work ethic of all citizens and the school environment.Keywords: Conceptual Models; Character Building. AbstrakTujuan dari penelitian ini adalah untuk memahami berbagai model pengembangan dalam penanaman nilai karakter di sekolah. Pendekatan yang digunakan adalah pendekatan kualitatif dengan teknik studi pustaka. Berdasarkan temuan dan analisis, ditemukan bahwa konsep pengembangan pendidikan karakter di sekolah merupakan model penanaman nilai-nilai karakter yang terdiri dari pengajaran, pembiasaan, dan peniruan, dalam implementasinya Model Tadzkirah, Istiqomah, Iqra – (Fikir – Zikir) Model merupakan model yang tepat untuk digunakan dalam pembelajaran pendidikan karakter, begitu juga dengan CTL. Selanjutnya proses pendidikan karakter perlu melibatkan seluruh komponen (stakeholder), termasuk komponen pendidikan itu sendiri, dan etos kerja seluruh warga dan lingkungan sekolah.Kata Kunci: Model Konseptual; Pembentukan karakter.